The Incidence Of Human Papilloma Virus In Pregnant Women and the Vertical Transfer Rate at Vaginal Delivery - Kurban, Yüksel; Alan, Yasemin; Uyar, Ibrahim; Sahin, Izzet; Sahin, Izzet (Progress in Nutrition, 2021)
Objective: Among 200 different genotypes of HPV at least 40 are related with anogenital diseases. HPV not only increases the risk of cervical and anogenital malignancies but also causes sexually transmitted infections in women in fertile period. In the past decades, the rate HPV infections have incerasd all over the world. The majority of infections are asymptomatic or presents with few small condylomas that can be ignored easily.It is clear that HPV infection is sexually transmitted, however there is lack of sufficient data about the fetomaternal transmission. The aim of this study is to determine the prevalance of Human Papilloma Virus (HPV) in Turkish society and to find the rate of the vertical transmission of HPV in the HPV positive mothers that give birth by vaginal delivery. Subject  and  Method: A total of 150 hospitalized women in full term with uterine contractions were enrolled in the study. Dacron swaps were taken from cervical canal of the hospitalized women and right after the delivery swaps were taken from the oro/nasopharynx of the babies.  The samples were analysed by Digene Hybrid Capture HPV DNA assay. Results: Among 150 women, 8 had ceserian section for some reason and the remaining  142 women and their babies were evaluated for HPV positivity. Eleven pregnant women (7.7%) were HPV positive and none of the babies had HPV positivity. Conclusion: When the complications of HPV infection are considered, this rate of HPV positivity can create a high medical problem in the near future.